Problems of investing in enterprises for processing and disposal of solid municipal waste - E. I. Shamanina; I. S. Arshinskaia (Вестник университета, 2022)
The issues of investing in enterprises engaged in the utilisation and processing of municipal solid waste are currently relevant due to increasing consumption, correspondingly increasing production and the amount of waste and require the most careful approach from the point of view of environmental security. The object of the research are the factors that determine the potential benefits of investing in enterprises of this industry. The methodological basis of the study was сompiled by general scientific methods of knowledge and the special scientific methods arising from it: logical, analytical, comparative analysis method, and information processing statistical methods. The authors present growth indicators in dividend payments and stock prices of individual American companies that provide services for the processing and waste disposal from those companies that operate in the residential sector, industry, and municipal organisations. The negative factors, hindering investment in this sector in Russia, have been reflected. The research results show the new development potential for the recycling and waste management industry.